(3UaI GdUahIs - (3YHO GdQMef Hf Ydj Hf eMeO GdLhRj GdbQTj GdHZOGOj, CHh GdaQL, GHf GdLhRj , J (B597 (3g` s; (3CHj fYje CMeO Hf YHO Gddg Hf egQGf GdCUHgGfj,J (B430 (3g` s
(3ChdgG (B:s
(3CeG HYO deG fXQJ ai cJGH MdjI GdChdjGA dCHj GdfYje GdCUagGfj QMeg Gddg CYLHc PcQ GdUGdMjf hGdCNHGQ hSCdJfj Cf GNJUQ Pdc aCbhd s
(3BNQgG (B:s
(3bGd GdRgQi(B: (3Med CSGeg Mjf eGJ ef GdLQa Edi GdeOjfI s
(3GfXQ Qbe (B1117 (3JGQjNs
(3GdeNWhW ef hba GdSjO CMeO YHOGdSdGe GdTjTfj GdMSfjs
(3hYdjgG Jedc HGSe eMeO Hf eMeO GdgQjOj GdMdHj GdOeTbjs
(3fSNI KGfjI s
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
Keywords: (3GdJGQjNs